Uji Daya Hambat Ekstrak Etanol Batang Saluang Belum terhadap Bakteri Escherichia coli: The Inhibitory Test of Ethanol Extract Saluang Belum Stem to Escherichia coli - Rezqi Handayani; Nurul Qamariah; Saftaria Ayu Mardova (Borneo Journal of Pharmacy, 2018)
Saluang Belum one of the herbal plants that have the benefits as a traditional medicine in Central Kalimantan. People in Central Kalimantan trusted Saluang Belum stem has an empirical benefit as a stamina enhancing agent and as an antioxidant. From previous research, Saluang Belum stem has a secondary metabolite that was saponin and tannin. Of these two secondary metabolites scientifically have pharmacological effects one of which was able to inhibit bacterial growth. To prove it in this research, the inhibitory test of ethanol extract of Saluang Belum stem from the growth of Escherichia coli bacteria. The inhibitory test method used in this study was the diffusion method using a variety of concentrations of 0.5%, 1%, 5%, 10%, and 15%. The result of this research, that there was no inhibition zone on the media used in all concentration. From these results can be concluded Saluang Belum stem ethanol extract unable to inhibit the growth of E. coli bacteria at concentrations of 0.5%, 1%, 5%, 10%, and 15%.